SEVERAL FACTORS INFLUENCE WIFE’S CONTRIBUTION THE INCREASE IN INCOME OF FISHERMEN FAMILY IN MANGGOPOH PALAK GADANG ULAKAN VILLAGE ULAKAN TAPAKIS SUB-DISTRICT PADANG PARIAMAN DISTRICT WEST SUMATRA PROVINCE - Ike Ratna Sari; Trisla Warningsih; Hamdi Hamid (Berkala Perikanan Terubuk, 2018)
This research aims to determine the type of work carried out by fishermen wife’s, calculate the amount of income earned by fishermen and contribution fishermen wife’s and analyze several factor influence wife’s contribution the increase income of fishermen family. This research was conducted in September 2018. The method used in this research were a survey method. Respondents taken in this study is 36 people, namely fishermen and fishermen wife’s that work. The results of this Penelitianresearch indicate the work carried out by fishermen wife’s such as rickety stalls, sewing, trade, rice stalls, morning absorption stalls, The mean of income the fishermen’s is IDR 1.568.106,-, the mean of income the fishermen wife’s is IDR 797.222,-, the mean of income the fishermen family is IDR 2.577.829,- and the contribution of fishermen’s wife is 32%. The results of the analysis are 94,6%. Factors that singnificantly influence the wifw’s contribution in increasing the income off the fishermen’s family are wife’s income, aducation, number of family dependents, work time bulk and spending.